Apostasy As a Reason For the Dissolution of Marriage - Yuyun Yulianah; Taufiq, Taufiq; Solihah, Cucu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Freedom to embrace religion is a human right that is protected by law, however, the Indonesian marriage law system does not recognize religious differences within the family. The act of leaving Islam (apostasy) affects the validity of the marriage and results in the dissolution of the marriage. Based on data obtained from the West Java Religious High Court regarding the dissolution of marriages due to apostasy, the authors try to examine it from a normative juridical basis regarding the reasons for apostasy being considered by religious courts and also the study of Islamic law (fiqhiyah) in terminating a marriage bond. The research method uses a qualitative approach in the form of a comparative analytical descriptive study, namely describing, describing, and disclosing data that is related to the research theme.